2021
DOI: 10.1103/physrevd.104.022004
|View full text |Cite
|
Sign up to set email alerts
|

Upper limits on the isotropic gravitational-wave background from Advanced LIGO and Advanced Virgo’s third observing run

Abstract: We report results of a search for an isotropic gravitational-wave background (GWB) using data from Advanced LIGO's and Advanced Virgo's third observing run (O3) combined with upper limits from the earlier O1 and O2 runs. Unlike in previous observing runs in the advanced detector era, we include Virgo in the search for the GWB. The results of the search are consistent with uncorrelated noise, and therefore we place upper limits on the strength of the GWB. We find that the dimensionless energy density ⌦GW  5.8 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
208
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 272 publications
(230 citation statements)
references
References 112 publications
(102 reference statements)
9
208
0
Order By: Relevance
“…The latest attempt to look for GW signals produced by cusps, kinks and kink-kink collisions has been done using the full O3 Run data of LIGO and Virgo [257], using three different models of cosmic string loop distribution. Although no detection for single short-duration transient signals has been found, constraints on the cosmic string tension Gµ have been derived from the SGWB energy density upper limits [246]. These constraints on the tension Gµ, as a function of the number of kinks per oscillation, of the Nambu-Goto strings, derived for different cosmic string loop distribution models, improve previous results in [258][259][260] by up to 2 orders of magnitudes.…”
Section: Cosmic Stringsmentioning
confidence: 62%
See 1 more Smart Citation
“…The latest attempt to look for GW signals produced by cusps, kinks and kink-kink collisions has been done using the full O3 Run data of LIGO and Virgo [257], using three different models of cosmic string loop distribution. Although no detection for single short-duration transient signals has been found, constraints on the cosmic string tension Gµ have been derived from the SGWB energy density upper limits [246]. These constraints on the tension Gµ, as a function of the number of kinks per oscillation, of the Nambu-Goto strings, derived for different cosmic string loop distribution models, improve previous results in [258][259][260] by up to 2 orders of magnitudes.…”
Section: Cosmic Stringsmentioning
confidence: 62%
“…Another kind of persistent signals are those forming the SGWB. For the case of isotropic stochastic searches, mainly based on cross-correlation methods, upper limits derived from the first three Observing Runs are given in [246]. Since the results of the search are consistent with uncorrelated noise, upper limits on the dimensionless energy density are reported, improving previous bounds by a factor of 6.0 for the flat background case.…”
Section: Persistent Signals In O3mentioning
confidence: 94%
“…In the Advanced LIGO's and Advanced Virgo's third observing run (O3), data from all three baselines were included in the isotropic GWB search. Combining O3 data with upper limits from the earlier first and second (O1 and O2) observing runs, it was found that the results are consistent with uncorrelated noise, hence placing upper limits on the strength of the GWB [37]. More precisely, performing a Bayesian analysis that allows for the presence of both a GWB and an effective magnetic background arising from Schumann resonances, no evidence of correlated noise of magnetic origin was found.…”
Section: Gravitational-wave Backgroundmentioning
confidence: 88%
“…Bayesian model selection was then used to distinguish between models that include correlated magnetic noise and those with a true GWB. This method, originally proposed [36] and used in the framework of LIGO/Virgo detectors [37], was consequently extended in the case of the third generation Einstein Telescope interferometer [38] forecasting the necessary measures to ensure that magnetic contamination will not pose a threat to the corresponding science goals. In particular, it was shown [38] that, for GWB searches below ∼30 Hz, it will be necessary for the Einstein Telescope magnetic isolation coupling to be two to four orders of magnitude better than the one measured in the current Advanced LIGO and Virgo interferometers.…”
Section: Gravitational-wave Backgroundmentioning
confidence: 99%
“…The corresponding GW spectra are displayed in the right panel; the scale of the phase transition covers many orders of magnitude, from ∼100 GeV to ∼PeV. The sensitivity of LIGO [47,48] and the future experiments, µAres [49], TianQin [50], Taiji [51], LISA [52], BBO [53], DECIGO [54], AEDGE [55], AION [56], ET [57], are also shown. Clearly, the scenario is testable at AEDGE, DECIGO, BBO and ET.…”
Section: Jhep10(2021)193mentioning
confidence: 99%